An endogenous growth approach on the role of energy, human capital, finance and technology in explaining manufacturing value-added: A multi-country analysis. Issue 7 (July 2020) - K, Arjun; Sankaran, A.; Kumar, Sanjay; Das, Mousumi
Abstract: The multi-dimensional benefits offered by the manufacturing sector in economic growth and development make academicians and policymakers to consider this sector still as an engine of growth . The unique qualities of this sector occupy a predominant place in the development policies around the world. Against these insights gained from economic literature, the study empirically investigates the role of energy, human capital, finance and technology in influencing manufacturing value-added in an endogenous growth framework by assessing short-run and long-run relation through ARDL bounds test approach followed by VECM causality test. The results testify the existence of energy-led, finance-led (supply leading), technology-led, and human capital-led growth hypotheses . These results give important insights and directions to have long term well-framed policy perspectives to develop financial institutions, the uninterrupted energy flow to the manufacturing sector, a blend of education and skill intensive programs and, an import strategy specially designed to obtain the spillover benefit of foreign technology. Abstract : Endogenous growth model; human capital; energy-led growth; finance-led growth; technology-led growth; and human capital-led growth; Economics; International trade; Economic Growth; Macroeconomics; Energy economics